Analisis Pemborosan Waktu Produksi Pada Bagian Perakitan Rumah Boneka Menggunakan Pendekatan Lean - Tiara Tiara; Surya Perdana (Teknik Industri Universitas Indraprasta PGRI, 2019)
CV. RB which is the object of this research is a manufacturing company producing wood-based doll houses. The purpose of this study is to evaluate waste and provide recommendations for improving the production process so that it can improve the efficiency of production time on the CV. RB. The lean production system gives a good change to the company. In solving the problems that are being faced, the analysis carried out in this study is the analysis of NVA and NVAN using fishbone diagram data analysis techniques in this study in terms of NVA and NVAN. In the process of assembling the pattern there are 27 worker activities, starting from the ground floor assembly to the left to the installation of tile on the right. based on the VA, NVA and NVAN classification in the sanding process, it can be seen that there are 30 wastes in the NVA classification with a percentage of time of 19.2%, there are 18 wastes in the NVAN classification with a percentage time of 0.6%. Based on observations on the production floor there is a waste of time in the process of assembling the pattern. This is caused by several factors, namely: material, human, environment and machinery. Some waste of production time is a pattern assembly process that results in long activities. waste contained in this assembly part is motion and waiting.